Static quark-antiquark potential in the quark-gluon plasma from lattice QCD - Burnier, Yannis; Kaczmarek, Olaf; Rothkopf, Alexander (Physical review letters, 2015)
We present a state-of-the-art determination of the complex valued static quark-antiquark potential at phenomenologically relevant temperatures around the deconfinement phase transition. Its values are obtained from nonperturbative lattice QCD simulations using spectral functions extracted via a novel Bayesian inference prescription. We find that the real part, both in a gluonic medium, as well as in realistic QCD with light u, d, and s quarks, lies close to the color singlet free energies in Coulomb gauge and shows Debye screening above the (pseudo)critical temperature Tc. The imaginary part is estimated in the gluonic medium, where we find that it is of the same order of magnitude as in hard-thermal loop resummed perturbation theory in the deconfined phase.